Academic Procrastination for Students of the Faculty of Psychology and Educational Sciences (FPIP) at the University: Prokrastinasi Akademik pada Mahasiswa Fakultas Psikologi dan Ilmu Pendidikan (FPIP) di Universitas - Izzati, Roudhotul; Nastiti, Dwi (Universitas Muhammadiyah Sidoarjo, 2022)
The research motivated by phenomenon of students experiencing academic procrastination. This study aims to describe the picture of academicprocrastination that occurs in the Faculty of Psyichology and Education, University of Muhammadiyah Sidoarjo (UMSIDA). This type of research uses a quantitative approach with a descriptive type of research. The research population is the students of the Faculty of Psichology and educational Sciences for the 2019-2020 academic year, totaling 2.000 students. The sample of this study was 249 students using the propotional random sampling technique. The research data collection technique used a psychological scale with a Likert scale type, namely the academic procrastination scale. The data analysis technique used descriptive statistics with the product moment correlation technique using the SPSS 19.0 for windows program. The results showed that overall all students of the Faculty of Psychology and educational Sciences (FPIP) at the University of Muhammadiyah Sidoarjo did academic procrastination, in this study it was 75,5%.